2020
DOI: 10.1073/pnas.2010281117
|View full text |Cite
|
Sign up to set email alerts
|

How synaptic pruning shapes neural wiring during development and, possibly, in disease

Abstract: At birth, an infant's brain is packed with roughly 100 billion neurons-some 15% more than it will have as an adult. As we learn and grow, our experiences strengthen the circuits that prove most relevant while the others weaken and fade."One extreme view of this would be that you start out wired up for every possible contingency," says Jeff Lichtman, a neuroscientist at Harvard University in Cambridge, MA. Over time, a large percentage of those wires are permanently disconnected, says Lichtman."What you're left… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
92
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(107 citation statements)
references
References 16 publications
(12 reference statements)
2
92
0
2
Order By: Relevance
“…In addition to situations where dysregulated pruning likely occurs at developmental stages, many recent data point to a reactivation of the pruning machinery in adults as a consequence of the decrease in synaptic activity that occurs during ageing or as a result of neuronal damage [ 48 ]. The loss of presynaptic terminals and dendritic spines, together with the activation of glial cells, are early pathogenic mechanisms that strongly correlate with CD in a number of neurodegenerative diseases.…”
Section: Overview Of Microglia and Synaptic Pruningmentioning
confidence: 99%
“…In addition to situations where dysregulated pruning likely occurs at developmental stages, many recent data point to a reactivation of the pruning machinery in adults as a consequence of the decrease in synaptic activity that occurs during ageing or as a result of neuronal damage [ 48 ]. The loss of presynaptic terminals and dendritic spines, together with the activation of glial cells, are early pathogenic mechanisms that strongly correlate with CD in a number of neurodegenerative diseases.…”
Section: Overview Of Microglia and Synaptic Pruningmentioning
confidence: 99%
“…Synaptic loss and dendritic atrophy have been reported for neurodevelopmental and neurodegenerative disorders like SCZ, MDD and Alzheimer disease (AD) (Lin and Koleske, 2010), suggesting a possible therapeutic strategy of maintaining normal dendritic architecture and restoring its related functions (e.g., synapse development). Perhaps preventing synaptic over-pruning during childhood and adolescence could be bene cial (Sakai, 2020). Supporting evidence from an earlier study showed that people chronically exposed to minocycline, an antibiotic with anti-in ammatory effects that reduces pruning, are at signi cant lower risk of incident psychosis (Sellgren et al, 2019).…”
Section: Discussionmentioning
confidence: 84%
“…In the healthy brain microglial processes are constantly contacting synaptic contacts located on neuronal dendrites. These microglia-dendritic contacts are instrumental for synaptic pruning in early development, which removes silent, aberrant or redundant synapses by en passant phagocytosis ( Sierra et al, 2010 ) thus contributing to shaping neuronal ensembles and supporting neuroplasticity ( Kettenmann et al, 2013 ; Sakai, 2020 ). Synaptic pruning is controlled by neuronal complement system ( Stevens et al, 2007 ; Schafer et al, 2012 ), which tags the synapses to be removed, and by neurone-derived chemokine CX3CL1 also known as fractalkine.…”
Section: Modes Of Microglial Patrolling Of the Healthy Cns: Role For mentioning
confidence: 99%